1992
DOI: 10.1002/hep.1840160517
|View full text |Cite
|
Sign up to set email alerts
|

Failure of Simple Biochemical Indexes to Reliably Differentiate Fulminant Wilson's Disease From Other Causes of Fulminant Liver Failure

Abstract: Serum, urine and tissue biochemical findings were studied in 21 cases of fulminant Wilson's disease with respect to the value of a recently described biochemical index based on serum alkaline phosphatase and total serum bilirubin levels, and these cases were compared with 193 other cases of fulminant liver failure. Serum bilirubin, alkaline phosphatase and AST levels found in fulminant Wilson's disease were significantly different from those found in other cases of fulminant liver failure, but differentiation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
1
1

Year Published

1993
1993
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(26 citation statements)
references
References 21 publications
2
21
1
1
Order By: Relevance
“…Berman et al (5) identified alkaline phosphatase to total bilirubin ratio of Ͻ2.0 and AST to ALT ratio of Ͼ4.0 for FWD diagnosis. Validity of these two indexes was not confirmed by other studies, which indistinctly analyzed patients with fulminant, subfulminant, acute-on-chronic, and chronic Wilson's disease (15,20,21). In our series, AP to total bilirubin ratio as well as AST to ALT ratio showed significant difference between both groups.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…Berman et al (5) identified alkaline phosphatase to total bilirubin ratio of Ͻ2.0 and AST to ALT ratio of Ͼ4.0 for FWD diagnosis. Validity of these two indexes was not confirmed by other studies, which indistinctly analyzed patients with fulminant, subfulminant, acute-on-chronic, and chronic Wilson's disease (15,20,21). In our series, AP to total bilirubin ratio as well as AST to ALT ratio showed significant difference between both groups.…”
Section: Discussioncontrasting
confidence: 79%
“…Of the ten published studies, six were issued from the same few centers, and most analyzed indistinctly adult and pediatric populations. Only Sallie and colleagues (21), in a study addressing diagnostic criteria, clearly identified a pediatric and an adult population: Among the 14 children they mentioned, four required ELT (29%) and all survived (100%). This surprisingly elevated survival rate raises a question about the type of studied population.…”
Section: Discussionmentioning
confidence: 96%
“…Assessing the prognosis of patients with ALF WD is critical in order to stratify patients who will improve spontaneously with supportive treatment from those who will need a liver transplantation . The couple of reports involving small number of patients from tertiary centers consist of a mix of both pediatric and adult patients, making comparison between series difficult . Two WD‐specific prognostic models have been published in the last two decades .…”
Section: Introductionmentioning
confidence: 99%
“…It is crucial that the entity of wilsonian fulminant hepatitis be clinically recognized because of its uniformly fatal outcome if liver transplantation is not performed in a timely fashion (13)(14)(15)(16)(17)(18). In this form of Wilson's disease, the features of hepatic insufficiency are associated with nonimmune hemolysis and, remarkably, with relatively low serum transaminase and alkaline phosphatase activities, considering the extent of hepatic necrosis (13,17,19).…”
mentioning
confidence: 99%